Clinical Utility and Alterations in Bacterial Flora in Fecal Microbiome Transplantation - Atman A. Dave; Rachel Robson (University Library System, University of Pittsburgh, 2015)
Dysbiotic states of gut ecology can be altered directly by transplantation of fecal preparation from healthy donors to patients with therapeutic intent. This paper assesses this fecal microbiota transplantation (FMT) in two respects: (1) the bacterial shifts in patient microbiomes with FMT and (2) clinical outcomes and variables of FMT. The PubMed database was searched using the MeSH terms "Feces/microbiology," "Microbiota," and "Transplantation." Thirteen papers found examined clinical outcomes and variables of FMT, and eight assessed metagenomic data and bacterial composition in the peri-FMT period. FMT was reported to have high cure rates in Clostridium difficile infection (CDI), generally increased levels of members of the phyla Bacteriodetes and Firmicutes, and decreased levels of members of Proteobacteria. Therapeutic FMT alters bacterial composition from a dysbiotic state pre-FMT to a healthy commensal state post-FMT in CDI patients, but further studies are necessary to understand its role in the treatment of other diseases